Health Human Resources Negligence: Is It The Hospital’s Responsibility? - Arimbi, Diah; Abdumurad Abdusaidovich, Khakberdiev (Jurnal Pembaharuan Hukum, 2024)
Hospitals are institutions fraught with the risk of legal action, as they are dense with resources, technology, knowledge, and the risk of health measures. Health human resources (medical personnel, health personnel, and supporting personnel) carry out their work based on standards determined by the government, their profession, and the hospital, with permanent employee status or an agreement/contract, forming an employment relationship. On this basis, the hospital is responsible for negligence committed by its workers. The Corporate Liability Doctrine demands that the hospital be responsible for its workers who make mistakes. Apart from this doctrine, the theory of vicarious liability also explains the same thing. However, all accusations of negligence to obtain compensation must, of course, require proof of error in the action. Furthermore, health law does not only require hospitals to be responsible for clinics or community health centers, not being included in this category even though legally they are both legal entities. Apart from that, the amount of compensation borne by hospitals and health resources has not been regulated in the provisions, so it needs to be determined jointly by both parties because both parties have legal responsibility.